Pengaruh Stres Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan pada PT Stanford Teknologi Indonesia - Ayu, Ayu Silvania Pandiangan; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this research is to determine the effect of work stress and compensation on employee job satisfaction at PT Stanford Teknologi Indonesia in Jakarta both partially and simultaneously. The data used in this study consisted of primary data collected through questionnaires against 75 respondents distributed to employees who worked at PT Stanford Teknologi Indonesia in Jakarta. The approach used was a quantitative approach and processed using SPSS 26. The results of the study show that work stress and compensation have a significant effect on employee job satisfaction at PT Stanford Teknologi Indonesia in Jakarta.